2012
DOI: 10.4172/2157-7110.1000206
|View full text |Cite
|
Sign up to set email alerts
|

Development of Probiotic Beverage from Whey and Pineapple Juice

Abstract: The aim of this study was to develop a probiotic beverage using whey and pineapple juice. Lactobacillus acidophilus was used as the probiotic organism. The level of pineapple juice addition was optimized on the basis of sensory quality evaluation. Fermentation time using 1 per cent inoculum of L. acidophilus was optimized on the basis of sensory quality evaluation, growth and activity in terms of pH and acidity. The 65:35 blend ratio of whey and pineapple juice fermented for 5 hr gave desirable results with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 7 publications
(6 reference statements)
3
20
0
2
Order By: Relevance
“…The similar result observation was reported by Shukla et al (2013) who reported that overall sensory score was higher for fruit based fermented beverage upto 10 days of storage. It was also observed from table 2 that overall acceptability was higher for beverage II than beverage I, this might be due to different metabolic activity and different acid production rate of these two different starter culture used for preparation of these two different beverages.…”
Section: Sensory Evaluation During Storagesupporting
confidence: 90%
“…The similar result observation was reported by Shukla et al (2013) who reported that overall sensory score was higher for fruit based fermented beverage upto 10 days of storage. It was also observed from table 2 that overall acceptability was higher for beverage II than beverage I, this might be due to different metabolic activity and different acid production rate of these two different starter culture used for preparation of these two different beverages.…”
Section: Sensory Evaluation During Storagesupporting
confidence: 90%
“…The guava juice which was selected as the medium had a pH of 6.The microbial population in the medium at 48 hr showed many colonies (TMTC) (Figure 2) (Table 1). After 72 hr of fermentation the microbial population dropped as it was expected [12].…”
Section: Resultsmentioning
confidence: 92%
“…The number of B. bifidus NCDC 255 bacteria in a whey beverage with aloe vera juice (whey to juice ratio was 70:30) was 7 log cfu/g and was stable during the 30-day storage period, although the pH decreased from 4.40 to 4.00 (Sasi Kumar, 2015). Shukla et al (2013), who analyzed whey-pineapple drinks (whey to pineapple juice ratio 65:35) containing L. acidophilus NCDC-015 probiotic strain, found similar results in the number of probiotic bacteria and pH during 28 days of storage. High survivability of the probiotic L. heleveticus strain MTCC 5463 in whey beverages with 10% orange juice and 1.5% inulin was reported by Shah et al (2016); during 28 days of storage the number of bacteria remained at a high level of 8 log cfu/g, while the pH of the beverage decreased from 3.82 to 3.67.…”
Section: Discussionmentioning
confidence: 99%